Qualitative evaluation of two London Faith and Health Networks: lessons learnt from a model of an interface between health systems and minority communities - Leonora G Weil; Tracey Chantler; Ben Kasstan-Dabush; Ana Zuriaga-Alvaro; Ella Johnson (BMJ Public Health)
Background Ethnic and religious minorities in the UK had a higher risk of severe illness and mortality from COVID-19 in 2020–2021, yet were less likely to receive vaccinations. Two Faith Health Networks (FHNs) were established in London in 2022–2024 as a partnership approach to mitigate health inequalities among Muslim and Jewish Londoners through a health system–community collaboration. By evaluating the FHNs, this study aimed to examine: the organisational processes required for FHNs to serve as a model of interface between health systems and minority communities; the role these networks play in addressing public health inequalities; and implications for their future development and sustainability.Methods A qualitative evaluation of the two FHNs was conducted using semi-structured interviews (n=19) with members of the ‘London Jewish Health Partnership’ and the ‘London Muslim Health Network’. Participant clusters included public health professionals, healthcare workers, community representatives and local government workers.Results The FHNs shared similar structures of leadership, but differed in core membership, which influenced their access to expertise and the activities developed. They were found to perform a key conduit role by integrating expertise from within the health system and faith communities to address the needs and expectations of underserved communities, with the ultimate goal of addressing health inequalities through the design of tailored campaigns and services. Emerging themes for developing an FHN model included enhancing their sustainability by determining funding allocation, strategic integration into health systems and identifying the appropriate geographical scope to sustain their impact. Further implications included recognition of intersectionality, addressing diverse needs within faith communities and trust-building approaches.Conclusion This evaluation offers insights into developing partnership models between faith-based organisations and health sectors to foster relationships with underserved communities. These findings provide valuable considerations for teams navigating the priority of health equity and community engagement as part of our learning from the pandemic to support the development of FHNs across different faith communities, not just for vaccine uptake, but to support the broader health and well-being of communities more widely.